Public-Private Partnership as a Challenge for EAEU Cooperation - Safarov, Shukhrat (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2018)
In this article the author analyzes perspectives on the Eurasian Single Economic Space’ concerning infrastructural investment projects. These perspectives are considered with a consideration of Public-Private Partnership (PPP) principles and the traditional framework of EAEU (Eurasian Economic Union) integration. The article examines national legal differences, such as the existence of regulations for PPPs, possible models for project realization and spheres where PPP could be used. The author also analyzes the characteristics of the most famous PPP projects in the EAEU. The purpose of the article is to identify practical recommendations for the development of public-private partnerships to further cooperation between the EAEU countries. This research stems from the study of international experiences of public-private partnerships, the adaptation thereof, and clarification of the necessary steps for the most efficient development of PPP in EAEU countries. As such, the following priority steps for EAEU countries are suggested: 1) EAEU countries should take steps to unite their respective legislative bases in terms of mutual compatibility so that public and private partners could act as inhabitants of the Union everywhere, removing not only customs barrier obstacles for them, but also additional tax restrictions; 2) EAEU countries should create an international council for problems and disputes pertaining to PPP which will include representatives of the countries of EAEU, representatives of the business and scientific communities and non-profit associations. Such a council was recommended to be set up at the United Nations during the third session of the United Nations Economic Commission for Europe on the problems of international public-private partnership, held in Geneva (Switzerland) on 18-19 April 2011; 3) EAEU countries should make use of practical experience in the implementation of interstate PPP projects. An example of a successful interstate PPP - the project for expansion and modernization of the international airport in Warsaw, through which more than 85% of all passengers of international flights have passed.